PERANCANGAN MANAJEMEN PROYEK SISTEM INFORMASI BERBASIS ANDROID PADA FITRI TAYLOR PAKAI METODE WATERFALL - Nur Nadilla (CV. Denasya Smart Publisher, 2024)
At Fitri Taylor there is no information system used. So, in this article the author created a prototype design for an effective Project Management Information System for receiving sewing orders using the Waterfall application development methodology. The waterfall method is used because of its ability to organize steps systematically from needs analysis to design. This research will focus on the stages in needs analysis, system design, and system prototype implementation. It is hoped that the design of this system will facilitate the process of receiving sewing orders, increase efficiency, and minimize errors in information management. The Waterfall method as the framework used is expected to be able to provide clear and structured guidance in developing a sewing information management system, so that it is hoped that it can improve customer service and strengthen the company's competitiveness in a competitive market.